Life cycle sustainability assessment of municipal waste management systems = Ocena cyklu życia w gospodarce odpadami komunalnymi - Schluchter, Wolf; Rybaczewska-Błażejowska, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The core element of all waste management systems that determines further treatment is the collection, transportation and sorting of waste. There is a spectrum of options that ranges from the complete source separation of waste with little or no consecutive sorting to the minimum separation at source and the consecutive central sorting of fully commingle waste.
Keywords: Ocena Cyklu Życia (LCA); odpady komunalne; ekologistyka; zrównoważony rozwój; life cycle assessment (LCA); municipal waste; eco-logistics; sustainability